Neonatal screening for cystic fibrosis. Issue 2 (February 1988) - Bowling, F; Cleghorn, G; Chester, A; Curran, J; Griffin, B; Prado, J; Francis, P; Shepherd, R
Abstract : Two groups of patients with cystic fibrosis were compared. The screened group, detected with an improved neonatal screening assay for immunoreactive trypsin, developed fewer chest infections requiring treatment and gained more weight than the unscreened group. Early diagnosis by screening seems to affect early morbidity.